Integrated Neonatal Support with Placental Transfusion and Resuscitation (Inspire): A Feasibility Study. (1st June 2016) - Irvine, L; Thomas, S; Mehrem, A Abou; Singhal, N; Kowal, D; Soraisham, A; Cooper, S; Stritzke, A; Murthy, P
Abstract: BACKGROUND: Compromised neonates do not receive placental transfusion (PT), but receive immediate cord clamping to facilitate resuscitation. Animal studies suggest possible benefit of resuscitation during PT. OBJECTIVES: To study the feasibility of initiating resuscitative care during PT for 90s in preterm infants. DESIGN/METHODS: We designed a mobile, battery powered resuscitation platform (iNSPiRe) that contains a scale, warm gel mattress, oxygen and air tanks, blender, T piece resuscitator, pulse oximeter (PO), and suction device (Fig. 1). Resuscitative care included initial steps, and respiratory support at 30s following Neonatal Resuscitation Program guidelines. Thermoregulation was maintained using a hat, warmed blankets, and gel mattress. Heart rate was auscultated at 30, 60 and 90s. PO was placed on the right wrist/hand. The cord was clamped at 90s. The baby and platform were mobilized from mother's bedside to a radiant warmer by one provider, while another provider maintained respiratory support. Once on the warmer, axillary temperature (AT) was measured. Resuscitation interventions and management during first 24 hours were recorded. RESULTS: Seven infants born vaginally, median (range) gestational age (GA) was 30 weeks (28 to 36) and birth weight 1500g (1270 to 2650), were managed using iNSPiRe. Table 1 shows time (T) to initiate interventions, cord pH and Apgar scores. Five infants received continuous positive airway pressure (CPAP) and one received positive pressure ventilation; none had hypotension, pneumothorax, or received surfactant. No incidence of intraventricular hemorrhage. CONCLUSION: It is feasible to commence resuscitative care during PT in infants ≥30 weeks' GA for 90s. Further research is needed to assess the feasibility in smaller and sicker preterm infants.